UNVEILING STUDENTS' CHALLENGES AND ATTITUDES TOWARDS PROJECT-BASED LEARNING IN ENGLISH-SPEAKING TERTIARY CLASSROOM - Syafryadin, Syafryadin; Binti Othman, Juliana; Amalia, Shynta; Wardhana, Dian Eka Chandra (LLT Journal: A Journal on Language and Language Teaching, 2024)
University students learning English as a Foreign Language (EFL) often struggle with speaking anxiety, limited practice opportunities, and performance pressure. This paper explores the challenges and attitudes of EFL university students towards Project-Based Learning (PBL) implemented in a speaking class at the tertiary level in the Indonesian context. The study included 35 university students from a public university in Indonesia. The researchers employed a mixed-methods approach to examine students' attitudes and challenges. Data were gathered through a questionnaire and semi-structured interviews. The analysis of the questionnaire revealed predominantly positive attitudes towards PBL. The interviews uncovered challenges, such as lack of confidence, pronunciation difficulties, time constraints, heavy workload, and performance anxiety. Despite these challenges, the students had positive attitudes, emphasising PBL's potential for enhancing speaking skills. The study recommends targeted interventions to address lingering challenges and refine PBL implementation.